Antecedents of Nurse Job Satisfaction at Dr.Midiyato Suratani Tanjungpinang Navy Hospital - Satriadi Satriadi; Anoesyirwan Moeins; Alex Zami (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of work-life balance and work fatigue on nurses' job satisfaction at Dr.Midiyato Suratani Tanjungpinang Navy Hospital. The methods used in this study are descriptive and verifiative studies. The data collection technique used questionnaires distributed to nurses at the Dr. Midiyato Suratani Tanjungpinang Navy Hospital. The population was 132 nurses. While the qualified sample was 100 nurses using the Isaac and Michael table with an error rate of 5%. Data analysis using multiple regression using the JASP program. The findings of this study stated that work-life balance and work fatigue had a positive and significant effect on job satisfaction variables. The magnitude of the variable contribution of work-life balance and work burnout was 20.8% to job satisfaction. While the remaining 79.2% was influenced by other variables such as work stress, work attachment, compensation and organizational culture that were not examined in this study.